Discordant electroencephalogram epileptiform activity and hemispherectomy in children with refractory epilepsy and encephaloclastic lesions: a case series. (8th September 2021) - Nagarajan, Lakshmi; Ghosh, Soumya; Palumbo, Linda; Lee, Sharon; Shipman, Peter; Dyke, Jason
Abstract : This is a case series of six children with unilateral cerebral palsy and hemispheric encephaloclastic lesions who were evaluated for epilepsy surgery. Seizure onset was in the neonatal period in three children, at 17 months in two, and at 5 years in one. Their ictal and interictal electroencephalogram (EEG) abnormalities showed paradoxical lateralization to the incorrect/'normal' hemisphere or showed bilateral abnormalities. After cautious discussion regarding the discordant electroclinical profile and implications for outcome, they proceeded to a functional hemispherectomy (between ages 4–11y) with good outcomes (at 1–10y follow‐up). Their clinical details, EEG findings, electrocorticography, neuroimaging, and histology are reported. Possible surgical candidacy should be evaluated early in children with refractory epilepsy, even those with complex profiles and discordant data from the different investigations. Contralateral or bilateral EEG abnormalities should not preclude consideration of hemispherectomy in children with refractory epilepsy, hemiparesis, and uniclastic lesions. Abstract : This case series is commented by Rydenhag on page 285 of this issue.